Don Juan DeMarco [videorecording (DVD)] - Coppola, Francis Ford, 1939-; Leven, Jeremy; Leven, Jeremy; Brando, Marlon; Depp, Johnny; Dunaway, Faye (New Line Home Video, 1998)
A psychiatrist rescues a young man who claims to be the legendary lover, Don Juan, and then becomes enmeshed in the young man's fantasies.